The Main Trends and Prospects of the Platform Economy in the Russian Federation - S. N. Ryabukhin; I. A. Kokorev; A. A. Safronova; O. D. Pokrovskaya; N. M. Fomenko (Мир новой экономики)
Relevance of information. The given article substantiates institutional, administrative and managerial, organizational and economical concepts aimed to develop platform economy of the Russian Federation. Such concepts specifically include the formation of a list of systemically significant operators in the platform economy with an established special status for state regulatory regime to provide them different state support of economic preferences. These concepts also comprise unified approaches to state regulation of digital economic processes, as well as unified conditions for cross-border turnover of goods, services and capital within the framework of international entities with participation of the Russian Federation (Shanghai Cooperation Organisation, Eurasian Economic Union). Objective. The article provides calculation of dynamics of aggregate capitalization of systemically significant operators of the platform economy in the Russian Federation within the time frame period of 2022–2024. It also provides comparative analysis of the growth rates capitalization of the platform economy and GDP, as well as it reveals the major trends and social-economic effects, which the domestic platform economy currently generates. Methods. The authors apply synthetic, analytic, deductive etc. methods, as well as econometric tools. Conclusions. One of the major findings of the article is the following: introduction of large-scale digital assets contributes to overcome contemporary challenges for the Russian international and domestic logistics.